Analysis of cardiovascular system of students in different periods of training (Experimental biology, 2016)
The study of individual characteristics of functional changes and adapt to stressful loads of students is one of the important physiological problems. The aim of the study was to investigate the changes in the parameters of the cardiovascular system of students with different levels of mental and emotional stress under the influence of the exam. Analysis of the results demonstrated that most of the students respond to the situation as an examination on stressor and experiencing significant psycho-emotional stress, which are reflected in the functional state of the cardiovascular system. Can also be said about the underdeveloped cardiovascular system and the students of psycho-physiological instability of the body. Nature of the reaction of the cardiovascular system in the psycho-emotional stress among students varies considerably depending on the subjective forecast of passing the examination.
Keywords: psycho-emotional stress; the level of anxiety; cardiovascular system.